Observations on a variant of compatibility - G. Jungck (International Journal of Mathematics and Mathematical Sciences)
We consider a variation of the concept of compatible maps introduced by Hicks and Saliga [1], and obtain generalizations ofresults by Hicks and Saliga and others.